Feminism in the Poem Tukhotibu Al-Mar’ah Al-Miṣriyah by Malak Hifni Nasif Based on Michael Riffaterre's Semiotics Concepts - Ayu Rizkia Silviana; Supardi (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2023)
This article aims to describe the application of Michael Riffaterre's semiotic theory to the poem Tukhatibu al-Mar'ah al-Miṣriyah by Malak Hifni Nasif, an Egyptian-born feminist fighter. This study uses a qualitative descriptive method that focuses on narrative accompanied by detailed sentence descriptions. The results of this study show that through heuristic and hermeneutic readings it is revealed that the poem reflects the poet's message or advice to Egyptian women in 1900, in which many women began to leave their headscarves as a symbol of feminism. The matrix is ​​in the form of the poet's hopeful advice for Egyptian women. The model is in the form of the feminist movement, and the Variants are found in the 2nd, 3rd, 5th, 7th and 9th stanzas, as well as the Hipogram in this poem, which is a book by the previous poet entitled